Superficial Effects of Different Finishing and Polishing Systems on the Surface Roughness and Color Change of Resin-Based CAD/CAM Blocks - Aydın, Numan (2021)
Objective: CAD/CAM blocks are widely used in dental restorations around the world. This study aimed to investigate the effects of different polishing and finishing systems on surface roughness and color change of resin-based CAD/CAM blocks. Material and Methods: In this study, material samples of 2×7×12mm were prepared. In three different experimental groups, surface polishing was carried out with one-step, two-step and multi-step polishing systems. The samples in one subgroup of each experimental group were polished with the diamond paste. Once the initial roughness and color values of the samples were measured using a profilometer and a spectrophotometer, the samples were immersed in coffee. Surface roughness and color change (∆E00) results were statistically analyzed using two-way variance analysis (ANOVA). Results: Finishing and polishing systems created significantly different levels of surface roughness on the hybrid ceramic block (Vita Enamic) but not on the composites block (Brilliant Crios, Grandio Blocs). While the two-step and multi-step finishing and polishing systems produced the lowest color change on hybrid ceramic blocks, one-step and two-step systems achieved this on composite blocks (p<0.05). In all test groups, the supplementary polishing performed after regular polishing procedures helped us reduce the surface roughness and color change on CAD/CAM blocks.  Conclusions: The findings obtained in this study suggest that one and two-step polishing systems are more suitable for resin-based composite CAD/CAM blocks; for hybrid ceramic CAD/CAM blocks, on the other hand, two and multi-step finishing and polishing systems seem to be more efficient concerning lower surface roughness and resistance to color changes.